COMPARATIVE ANALYSIS OF THE OCCURRENCE OF HYPERMOBILITY OF JOINTS IN CHILDREN'S POPULATION OF TVER AND OTHER REGIONS OF THE RUSSIAN FEDERATION - I. I. Ivanova; S. F. Gnusaev; I. I. Makarova; А. А. Ivanova ("Paediatrician" Publishers LLC, 2014)
Aim: To assess the frequency of occurrence and the intensity of hypermobility of joints in children and teenagers of Tver in comparisonwith other regions of the Russian Federation. Patients and methods: 564 children and teenagers at the age from 3 to 17 years were examined. The presence of hypermobility of joints was determined by Beighton method. Anthropometrical measurements were taken, physical development of children was assessed. Results: The hypermobility of joints is characteristic practically for all children at the age of 3-4 years and most of children of 5-7 years. On average it meets in 71% of children of a preschool age and 31% of school students of Tver, making 35-40% in children of midchildhood; it is noted in every fourth child of 13-15 years and every tenth 16-17-year-old teenager. The hypermobility of joints of girls is 20% more than of boys. The high-grade hypermobility is characteristic for tall and thin teenagers; in midchildhood the children who in comparison with agemates are smaller in growth and weight are more flexible. The article presents the comparison of own data with the results of other similar researches. Conclusion: The frequency of occurrence of hypermobility of joints considerably differs in different age groups of children. The increased flexibility is physiological norm for the majority of preschool children, further it decreases in direct ratio to the age of a child.